The proposition of a new method to convert formalin cadavers to academic and museology purposes (Research, Society and Development, 2021)
The embalming of a cadaver to study anatomy in humans, animals, and for expositions in biological museums is classically performed by formaldehyde injection. Despite its efficiency and wide application, this method delivers technical problems and high toxicity. Through an experimental model with Wistar rats previously embalmed in formalin, we developed two converting solutions (G1 and G2) to perform a macroscopic and qualitative analysis of the embalming maintenance, the color, the fungus proliferation, the pliability, and the post-conversion dissection of the specimens. This work aims to present the results of this experiment and discuss the data. After 365 days of the experiment, both solutions showed benefits in terms of reduction of toxicity, the use of a single solution to convert, storage without the need for containers with embalming solution, containment of fungus proliferation, and improvement of the color of the organs. Although these are the initial results without full achievement, we consider the G1 solution a suitable and advantageous alternative for the museology area.